2021
DOI: 10.3390/foods10112801
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling of Canola Oil Biodegradation and Optimisation of Biosurfactant Production by an Antarctic Bacterial Consortium Using Response Surface Methodology

Abstract: An Antarctic soil bacterial consortium (reference BS14) was confirmed to biodegrade canola oil, and kinetic studies on this biodegradation were carried out. The purpose of this study was to examine the ability of BS14 to produce biosurfactants during the biodegradation of canola oil. Secondary mathematical equations were chosen for kinetic analyses (Monod, Haldane, Teissier–Edwards, Aiba and Yano models). At the same time, biosurfactant production was confirmed through a preliminary screening test and further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Zahri et al [2] studied the degradation of waste canola oil and pure canola oil using a consortium of native Antarctic soil bacteria. Zahri et al [3] also confirmed that the Antarctic soil bacterial consortium (reference BS14) are able to biodegrade canola oil. In addition, kinetic studies were carried out to examine the ability of BS14 to produce biosurfactants via a biodegradation process.…”
mentioning
confidence: 87%
“…Zahri et al [2] studied the degradation of waste canola oil and pure canola oil using a consortium of native Antarctic soil bacteria. Zahri et al [3] also confirmed that the Antarctic soil bacterial consortium (reference BS14) are able to biodegrade canola oil. In addition, kinetic studies were carried out to examine the ability of BS14 to produce biosurfactants via a biodegradation process.…”
mentioning
confidence: 87%